Determination of uranium and thorium in soil and plant parts around abandoned Lead–Zinc–Copper mining area - Şaşmaz, Ahmet; Yaman, Mehmet (My University, 2008)
This study reports distribution of uranium (U) and thorium (Th) in soil samples and the roots and shoots of some plants grown around an abandoned lead (Pb)–zinc (Zn)–copper (Cu) mining area. The plants Euphorbia macroclada, Verbascum cheiranthifolium Boiss, and Astragalus gummifer were examined. The determinations of U and Th were carried out by inductively coupled plasma-mass spectrometry (ICP-MS). Uranium and Th levels of the studied soil samples were found to be in the range of 1.1–70.3 mgkg21 and 2.1–62.1 mgkg21, respectively. Some results obtained from this study were higher than the mean U and Th concentrations of soils reported around the world. Uranium and thorium concentrations in studied plant roots were in the range of 0.04–16 and 0.08– 14.57mg kg21, whereas in plant shoots they were 0.02–2.76 and 0.07– 12.3mg kg21, respectively. It was concluded that the shoots of Astragalus and roots of Euphorbia and Verbascum can be used as both a biomonitor for environmental pollution and biogeochemical indicator because of their higher U and Th concentrations.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Biomonitor; Hyperaccumulator; Plant and soil contamination; Thorium; Uptake of toxic metals; Uranium